Household Diversity and the Impacts of COVID-19 on Families in Portugal - Gouveia, Rita; Ramos, Vasco; Wall, Karin (Frontiers in Sociology, 2021)
Throughout the world, the COVID-19 pandemic disrupted family routines, relationships, projects and sociability, threatening the health, income, social cohesion, and well-being of individuals and their families. Lockdown restrictions imposed during the first wave of the pandemic challenged the theories, concepts, and methods used by family sociologists and the intersecting fields of gender and social inequality. By restricting physical interactions to co-resident family members, the household regained a privileged role as a crucial social laboratory for studying the impact of COVID-19 on family life. The difficulties encountered by individuals in maintaining and dealing with close relationships across households and geographical borders, in a context in which relational proximity was discouraged by the public authorities, exposed the linked nature of family and personal relationships beyond the limits of co-residence. The main aim of this article is to investigate the social impacts of the pandemic on different types of households during the first lockdown at an early stage of the pandemic in Portugal. Drawing on an online survey applied to a non-probabilistic sample of 11,508 households between 25 and 29 March 2020, the authors combined quantitative and qualitative methods, including bi-variate inferential statistics, cluster analysis and in-depth case studies. The article distinguishes between different household types: solo, couple with and without children, extended, friendship, lone-parent families, and intermittent arrangements, such as shared custody. A cross-tabulation of the quantitative data with open-ended responses was carried out to provide a refined analysis of the household reconfigurations brought about during lockdown. The analysis showed how pre-existing unequal structural living conditions shaped the pathways leading to household reconfiguration as families sought to cope with restrictions on mobility, social distancing norms, and other lockdown measures. The findings stress that, in dealing with a crisis, multilevel welfare interventions need to be considered if governments are to cater to the differentiated social needs and vulnerabilities faced by individuals and families.